Hãy luôn nhớ cảm ơn và vote 5*
nếu câu trả lời hữu ích nhé!
a)2x(x-5)-12(5-x)=0
⇔2x(x-5)+12(x-5)=0
⇔(x-5)(2x+12)=0
⇔ [x−5=02x+12=0
⇔ [x=0+52(x+6)=0
⇔ [x=5x+6=0
⇔ [x=5x=0−6
⇔ [x=5x=−6
Vậy x∈{5;-6}
_______________________________________________________________
b)(5x-1)2-(2x+3)2=0
⇔[(5x-1)-(2x+3)][(5x-1)+(2x+3)=0
⇔(5x-1-2x-3)(5x-1+2x+3)=0
⇔(3x-4)(7x+2)=0
⇔ [3x−4=07x+2=0
⇔ [3x=0+47x=0−2
⇔ [3x=47x=−2
⇔ [x=43x=−27
Vậy x∈{43;-27}
#maingoctranthi
Hãy giúp mọi người biết câu trả lời này thế nào?
Bảng tin